In-Silico Study of Brassinosteroid Signaling Genes in Rice Provides Insight Into Mechanisms Which Regulate Their Expression - Ahmar, Sunny; Gruszka, Damian (Frontiers in Genetics, 2022)
Brassinosteroids (BRs) regulate a diverse spectrum of processes during plant growth and development and modulate plant physiology in response to environmental fluctuations and stress factors. Thus, the BR signaling regulators have the potential to be targeted for gene editing in order to optimize the architecture of plants and make them more resilient to environmental stress. Our understanding of the BR signaling mechanism in monocot crop species is limited compared to our knowledge of this process accumulated in the model dicot species - Arabidopsis thaliana. A deeper understanding of BRs signaling and response throughout plant growth and adaptation to continually changing environmental conditions will provide insight into mechanisms that govern the coordinated expression of BRs signaling genes in rice (Oryza sativa) which is a model for cereal crops. Therefore, we performed a comprehensive and detailed in silico analysis of promoter sequences of rice genes encoding components of the BR signaling. We used different bioinformatics tools and performed in silico study, including chromosomal mapping, phylogenetic relationships, transcriptional factor binding sites (TFbs) analysis, identification of cis-regulatory elements, tandem repeats, and the CpG/CpNpG islands. Additionally, we examined the expression profiles of these genes in various tissues during different developmental stages. In this study, a model of interactions between the encoded proteins was also analyzed. The obtained results revealed that the promoters of 39 BR signaling genes were involved in various regulatory mechanisms and interdependent processes that influence growth, development, and stress response in rice. The in-silico analysis of BRs signaling genes in O. sativa provides information about mechanisms which regulate the coordinated expression of these genes during rice development and in response to other phytohormones and environmental factors. Since rice is both an important crop and the model species for other cereals, this information may be important for the understanding of the regulatory mechanisms which modulate the BR signaling in monocot species. It can also provide new ways for the plant genetic engineering technology by providing a novel potential target, either cis-elements or transcriptional factors, to create elite genotypes with desirable traits.